YEAST PROBIOTICS WITH POTENTIAL TO ASSIMILATE CHOLESTEROL IN VITRO - Yan Ramona; Ni Luh Putu Ariwathi (SEAMEO BIOTROP, 2022)
In the last two decades the use of yeasts as new probiotics has increased significantly. Therefore, our current research was focused on the investigation of yeasts for novel probiotic development in Bali. The main objectives of this research were to isolate and characterize yeasts isolated from ragi tape (dried mix cultures of microorganisms normally used in the fermentation of rice or cassava in Indonesia) and tape ketan (fermented sticky rice) for possible use as yeast-based novel probiotics, with capability to assimilate cholesterol in vitro. In this study, the potential yeast isolates were evaluated for survival at low pH conditions (pH 2, 3, or 4) and in high levels of sodium deoxicholic (NaDC), at concentrations of 0.2, 0.4, or 0.6 mM. In addition, the yeast isolates were also evaluated for their ability to assimilate cholesterol in vitro and to elucidate biotransformation of cholic acid into deoxycholic acid. This study led to 10 isolates that were resistant to pH levels of 2, 3, or 4 and to NaDC at concentration of higher than 0.4 mM. Most of those isolates were also found to assimilate cholesterol in vitro at the rate of between 18% and 76% in 24 hours incubation. In the biotransformation test, none of those isolates transformed cholic acid into deoxycholic acid, indicating that they are safe and have potential to be developed into novel probiotics, either for human or cattle